ANALISIS STRATEGI FUNDRAISING ORGANISASI PENGELOLA ZAKAT DI ERA DIGITALISASI - Yuliar, Ade (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2021)
Zakat potential in Indonesia is very large, but the potential has not been explored optimally. One of the challenges is how zakat institutions create innovative strategies of collecting zakat in accordance with the current millennial era. This study aims to analyze zakat fundrasing models that have been done by zakat institutions and also attempt to propose solutions to optimize zakat funding in the digital era. The results of the research formulate that digital era funding strategy must be in line with the revolutionary spirit of industry 4.0 characterized by digital-based. So far the fundraising strategy is not yet new, that is still conservative for example: not yet make the website become based on android, so website more accessible. Zakat institutions also should innovates zakat payment cooperation as online zakat (online payment or e-payment), for example cooperation through fintech and e-commerce. Suggestions and conclusions that all zakat institutions have similarities, no new strategy and zakat institutions should innovate in strategy.Â Potensi zakat di Indonesia sangat besar, namun potensi tersebut belum tergarap secara maksimal. Salah satu tantangannya adalah bagaimana lembaga zakat menciptakan strategi inovatif dalam menghimpun zakat sesuai dengan era milenial saat ini. Penelitian ini bertujuan untuk menganalisis model-model fundrasing zakat yang telah dilakukan oleh lembaga zakat dan juga berupaya memberikan solusi untuk mengoptimalkan pendanaan zakat di era digital. Hasil penelitian merumuskan bahwa strategi pendanaan era digital harus sejalan dengan semangat revolusioner industri 4.0 yang bercirikan berbasis digital. Sejauh ini strategi fundraising masih belum baru, yaitu masih konservatif misalnya: belum menjadikan website berbasis android, sehingga website lebih mudah diakses. Lembaga zakat juga harus melakukan inovasi kerjasama pembayaran zakat sebagai zakat online (pembayaran online atau e-payment), misalnya kerjasama melalui fintech dan e-commerce. Saran dan kesimpulan bahwa lembaga zakat memiliki kesamaan,yaitu tidak ada strategi baru dan lembaga zakat harus berinovasi dalam strategi fundraising.